2020
DOI: 10.48550/arxiv.2010.07216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical Layer Security for V2I Communications: Reflecting Surfaces Vs. Relaying

Abstract: Wireless vehicular network (WVN) is exponentially gaining attention from industries and researchers since it is the Keystone of intelligent transportation systems (ITS). Despite the sophisticated features and services that it can offer, it is susceptible to networking attacks such as eavesdropping threats where the confidential transmitted signal could be overheard by a malicious entity. In this paper, we intend to study the physical layer security (PLS) where we consider the eavesdropping attack for vehicle-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Applying identity [49, 07.34.21.0012.01] in (7), we get (5). The derived PDF in (5) does not have any constraint on the parameters of dGG as present in the Meijer's-G representation [37].…”
Section: Statistical Results For Cascaded Channelsmentioning
confidence: 99%
“…Applying identity [49, 07.34.21.0012.01] in (7), we get (5). The derived PDF in (5) does not have any constraint on the parameters of dGG as present in the Meijer's-G representation [37].…”
Section: Statistical Results For Cascaded Channelsmentioning
confidence: 99%
“…Furthermore, PLS for multiple-input multipleoutput (MIMO) systems has been analyzed considering Nakagami-𝑚 fading under optimal, sub-optimal, and transmit antenna selection scheme [17]. Several studies look into two vehicular network system models: one with vehicle-to-vehicle communication and a RIS based access point as the source, and the other as a vehicular adhoc network (VANET) with a RIS-based relay mounted on a building [18][19][20]. Due to their ease of deployment and variable configuration, RIS-based technologies can be targeted for mobile nodes in vehicle networks.…”
Section: Related Workmentioning
confidence: 99%
“…Although several prior research [3,4,[18][19][20] assumed quasi static node positions for simplicity of analysis, the mobility effect of nodes has been proven to impair the performance of vehicular nodes. However, it has recently been demonstrated that adopting a real-time tuneable RIS can successfully mitigate rapid changes in received signal strength caused by the doppler effect.…”
Section: Motivations and Noveltymentioning
confidence: 99%
“…In addition, some other works also leverage RIS for security purposes, for example [19] suggested that RIS can help in alleviating security breaches related to eavesdropping. In [20], the authors studied the security issues related to eavesdropping attacks under different circumstances including active and passive relays (RIS).…”
Section: Related Workmentioning
confidence: 99%
“…In line with our proof and discussion above, we carry out three experiments to see the achievable minimum average bit rate for multi-user scenario. We set x R = 0, x I = [10,20,30,40,50]. Vehicles are generated by SUMO.…”
Section: A Ris Placementmentioning
confidence: 99%